EFEKTIVITAS TEPUNG JINTAN HITAM (Nigella sativa) UNTUK MENCEGAH INFEKSI Aeromonas hydrophila PADA IKAN PATIN - Dontriska .; Ade Dwi Sasanti; Yulisman . (Universitas Sriwijaya, 2014)
ABSTRACT This study aims to test the effectiveness of black cumin flour (N. sativa) was added to the feed to prevent infection by A. hyrophila on catfish. Catfish fed black cumin flour added as much as 0%, 5%, 10%, 15%, and 20% for 14 days, then tested for bacterial challenge with A. hydrophila 106 cfu.ml-1 through immersion. The results showed that administration of black cumin significantly (P <0.05) in the prevalence and survival of catfish, but not significantly (P> 0.05) on the growth of catfish. Black cumin was also able to increase the number of leucocytes and hematocrit levels. The best treatment in this study was the addition of black cumin as much as 15% in the feed, resulting in a prevalence of 2.22%, 88.33% survival, growth weight 2.51 grams, hematocrit 32%, and total leukocyte 14.88 x 104 sel.mm-3. Keywords : Black cumin, prevalensi, survival rate, leucocytes, hematocrit